Experimental substantiation of the effectiveness of the “massage” retinal veins for treatment of retinal vein occlusion - A. A. Krylova; O. I. Krivosheina; O. I. Urazova (Бюллетень сибирской медицины)
Objective: evaluate the effectiveness of treatment of retinal vein occlusion with the use of “massage” of retinal veins on the experimental model of photoinduced retinal venous occlusive disease.Materials and methods. Studies were carried out on 30 rabbits of the Chinchilla breed (30 eyes) weighing 1.5–2.0 kg. In the first stage of the experiment, for all animals the photoinduced thrombosis were modeled by laser irradiation of its retinal veins for 0.3–0.4 seconds at a density of 200 J/cm2 and a wavelength of 662 nm after the administration of “Photoditazine” at a dose of 2.5 mg/kg weight. In the second stage of the experiment, the animals were divided into the main group and the comparison group, depending on the method of treatment: 15 animals of the main group with “massage” of the retinal vein in the form of 5–7 movements with a silicone tip of the scanner Tano, 15 animals of the comparison group with epiretinal administration of recombinant prourokinase in a dose 500 international units (IU).Results. The formation of a parietal thrombus in the simulation of photoinduced the central retinal vein occlusion in the experiment leads to a slowing of perfusion in the affected vessel by (8.0 ± 2.5) s (according to fluorescence angiography), an increase in the thickness of the central parts of the retina by (70.2 ± 9.7) μm (according to optical coherence tomography), to the appearance of crimp and uneven lumen of the retina veins, extensive plasma and hemorrhages (according to the data of ophthalmoscopy). On the model of retinal veins thrombosis, a new method of treating retinal vein occlusion was tested, which showed significant efficacy. It has been established that the use of “massage” of the affected retinal vein reduces the time of venous perfusion by 1.3 times and 1.45 times accelerates the resorption of the edema of the central parts of the retina compared to enzymatic thrombolysis.Conclusions. “Massage” of the retinal veins is an effective method of treating retinal vein occlusion and is not accompanied by damage to chorioretinal structures during manipulation.